Between the Classics of Both Worlds : An Excursion to the MacCormack Library - Sánchez Martínez, César Félix (2019)
Sabine MacCormack’s legacy, inherited by the Instituto de Pastoral Andina, is one of the best collections now in Peru in the fields of Andean Colonial Chronicles and Latin Classics and it is also a living testimony that explains her peculiar intellectual approach.